Risiko Peran Media Terhadap Kejadian Sectio Caesarea Non Medis Di Rumah Sakit Bersalin Budi Mulia Makassar - Sukmawati (Jurnal Keperawatan Muhammadiyah, 2025)
Introduction : In recent years, goverments anda clinicians have expressed concern about the increasing rate of caesarean births and the negative concequences for maternal and infant health. Given the alarming rise ini caesrean section rates, in order the develop and implement safe and successful to reduce unnecessary caesarean deliveries, it is important to examine the factors contributing to this trend Objective : The study aimed to assess the risk of the role of the media in the incidence of nonmedical caesarean section. Method : This study uses a case control design with a sample of 100 people selected before determining the case and control randomly. The analysis used was chi square and odds ratio by looking at the significance of a = 0.05 and QR values. Data collection techniques by observation, interviews, and documentation. The type of data taken is primary data obtained by researchers from the results of direct data collection by distributing questionnaires to respondents. Results : The results of the study showed the influence of the media on the incidence of the nomedic caesarean section with a value of p = 0,000. Conclusion: Based on the results of the study it was concluded that the media had an influence on the incidence of nomedic caesarean section.